From source to bedside: Translational studies of centella asiatica for Alzheimer's disease: Human/Human trials: Other. (7th December 2020) - Wright, Kirsten M.; Magana, Armando Alcazar; Bollen, Melissa; Caruso, Maya; Gray, Nora E.; Matthews, Donald G; David, Jason C.; Mepham, Brigitte; Stevens, Jan F.; Maier, Claudia S.; Quinn, Joseph F.; Soumyanath, Amala
Abstract: Background: Centella asiatica (CA) is a botanical from Eastern medicine reputed to enhance cognition. Preclinical studies on CA and its bioactive components (triterpenoids and caffeoylquinic acids) strongly support its potential as a phytotherapeutic agent for aging, cognitive decline, and Alzheimer's disease (AD) through influences on antioxidant response, mitochondrial activity, tau phosphorylation, and synaptic density. Translation from preclinical models to humans, and developing an optimized, reproducible product for use in aging and AD clinical trials, present particular challenges for phytotherapeutic agents compared to single chemical entities. Method: To perform translational studies, a comprehensive scientific approach was developed including: identifying an optimal dose range for clinical evaluation, analysis and characterization of phytochemical variability, assessment for contamination and adulteration of raw material, formulation and manufacture of a stable botanical intervention and matching placebo, and application to a human pharmacokinetic trial (NCT03929250). Two doses of a custom made CA water extract product (2g and 4g) were administered orally to eight healthy elders (n=4 female, n=4 male) on two separate days. Plasma was collected over 12 hours to determine bioavailability and analyzed using reversed phase liquid chromatography‐tandem mass spectrometry. Result: The maximum plasma concentration (Cmax ) of the bioactive triterpenoids (1‐1.6µM) occurred at two hours (Tmax ) after oral administration. Conclusion: A robust scientific approach is necessary to address the complexity and variability of raw botanicals and botanical extracts for AD. Triterpenoids from CA water extract are orally bioavailable in humans.